District Size, Teacher Qualifications, and Pupil Performance in Maine School Districts - Richard Moreau (Journal of Research in Rural Education, 1987)
This study examines the relationships between district size, faculty educational qualifications and academic achievement in Maine's eighth grade students. Such relationships are often posited in the educational literature [3; 6; 16; 21]. Mean grade eight scores in mathematics, reading, and writing on the 1985 Maine Assessment Test are utilized as the measure of pupil performance. Aggregated to the school system level, these scores are often considered to be indicators of educational quality [12]